Efeito dos lasers de Nd:YAG e de Er:YAG na adaptação das obturações de canais radiculares: análise do selamento marginal apical - Carvalho, Cláudio Antonio Talge [UNESP] (2015)
The capacity of the laser to promote the cleaning and disinfection of the radicular canal system has been turning this type of treatment in a viable and real alternative in endodontics. The purpose of this study was to evaluate the apical marginal sealing of root canal obturations done after the irradiation with the laser of Nd:YAG or of Er:YAG. ln this manner, 42 human extracted single-rooted teeth were used, they were crown sectioned and the root canals prepared to n° 70 K file followed by back stepping with the nº 80 K file. The canals were irrigated abundantly with 1-% sodium hypochlorite solution. After they were dried and divided in 3 groups in agreement with the canal wall treatment. Group 1: the canals were filled with EDTA for 3 minutes, followed by irrigation with 1-% sodium hypochlorite solution; Group 2: the canal walls were irradiated with Nd:YAG laser; and Group 3: the canal walls were irradiated with Er:YAG laser. Afterwards, the root canals of all the specimens were obturated with gutta-percha cones and Top-Seal cement, by the lateral condensation technique. The roots were externally waterproof, except in the apical foramen and, immerged in aqueous solution of 2% methylene blue during 48 hours. The results showed that the largest infiltrations happened in the Group 3- Er:YAG (7.3mm), proceeded by the Group 1 - EDTA (1.6mm) and for the Group 2- Nd:YAG (0.6mm). The Group Er:YAG differed statistically of the others (p<0,05). lt was concluded that the Er:YAG laser application, previously to the obturations of radicular canals, must be used with caution until future research is define the best parameters for it's use